Variability of Internal Wave Strain Over the Western Boundary Region in the North Atlantic - Fan, Liming; Wang, Xin (Frontiers in Earth Science, 2022)
Based on the CTD profiles and mooring measurements of the Line W program in the North Atlantic about 35°N/70°W, we investigated the spatial variability of internal wave-induced strain variance along the Line W section and the associated reasons. The results showed that the internal wave strain variance over the slope could be up to five times larger than that in the interior. We have validated that internal tides and near-inertial waves were not the crucial processes for causing this variability. Meanwhile, we found that the high-frequency internal waves generated by the interaction of anticyclonic eddy and low-frequency internal waves may be a potential cause of strain enhancement. This study implies a potential route of mesoscale eddies to enhance the strain variance induced by internal waves.